Core concepts in sociology - Ryan, J. Michael (Hoboken, New Jersey Wiley, 2019)
Core Concepts in Sociology is a comprehensive guide to the essential concepts relevant to the current study of the discipline and wider social science. The contributing authors cover a wide range of concepts that remain at the heart of sociology including those from its academic founding and others much more recent in their development. The text contains contributions from an international panel of leading figures in the field, utilizing their expertise on core concepts and presenting an accessible introduction for students.

Drawing on the widest range of ideas, research, current literature and expert assessment, Core Concepts in Sociology contains over 90 concepts that represent the discipline. Coverage includes concepts ranging from aging to capitalism, democracy to economic sociology, epistemology to everyday life, media to risk, stigma and much more.

Written for students, researchers and wider professionals with an interest in the field of sociology, Core Concepts in Sociology offers a concise, affordable and accessible resource for studying the underpinnings of sociology and social science.
Includes bibliographical references and index.
Keywords: Sociology